(untitled) (translation. a transdisciplinary journal, 2022)
If hybridity is heresy, then to blaspheme is to dream. To dream not of the past or present, nor the continuous present; it is not the nostalgic dream of tradition, nor the Utopian dream of modern progress; it is the dream of translation as ‘survival’ as Derrida translates the ‘time’ of Benjamin’s concept of the after-life of translation, as survivre, the act of living on borderlines.